Unravelling the Role of P300 and TMPRSS2 in Prostate Cancer: A Literature Review - Gioukaki,C.; Georgiou,A.; Gkaralea,L.E.; Kroupis, C.; Lazaris, AC; Alamanis, C.; Thomopoulou,G.E. (Int.J.Mol.Sci., 2023)
Prostate cancer is one of the most common malignant diseases in men, and it contributes significantly to the increased mortality rate in men worldwide. This study aimed to review the roles of p300 and TMPRSS2 (transmembrane protease, serine 2) in the AR (androgen receptor) pathway as they are closely related to the development and progression of prostate cancer. This paper represents a library-based study conducted by selecting the most suitable, up-to-date scientific published articles from online journals. We focused on articles that use similar techniques, particularly those that use prostate cancer cell lines and immunohistochemical staining to study the molecular impact of p300 and TMPRSS2 in prostate cancer specimens. The TMPRSS2:ERG fusion is considered relevant to prostate cancer, but its association with the development and progression as well as its clinical significance have not been fully elucidated. On the other hand, high p300 levels in prostate cancer biopsies predict larger tumor volumes, extraprostatic extension of disease, and seminal vesicle involvement at prostatectomy, and may be associated with prostate cancer progression after surgery. The inhibition of p300 has been shown to reduce the proliferation of prostate cancer cells with TMPRSS2:ETS (E26 transformation-specific) fusions, and combining p300 inhibitors with other targeted therapies may increase their efficacy. Overall, the interplay between the p300 and TMPRSS2 pathways is an active area of research
Keywords: antagonists & inhibitors; Biopsy; genetics; Humans; Male; metabolism; Oncogene Proteins,Fusion; p300-CBP Transcription Factors; pathology; Prostate; Prostatic Neoplasms; Serine Endopeptidases; Transcriptional Regulator ERG